The Role of Local Government in Creating Business Sustainability: Case Study on Keris MSMES in Aeng Tong-Tong Village - Noerhalifah, Rohatina; Hafidhah, Hafidhah; Herli, Mohammad (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to determine the role of the Sumenep Regency government in creating business sustainability for Keris MSMEs in Aeng Tong-tong Village. Methodology/approach: Research conducted using qualitative research types. The types of data in this study are subject and documentary data. The data sources used are primary data and secondary data. Data collection techniques carried out by researchers use observation, documentation and interviews. Findings: The results of this study show that the role of the government in creating Business Sustainability in MSMEs is in the form of promotions, exhibitions, cost assistance for jamming, and coaching through tourism awareness groups (pokdarwis). Apart from that, the people of Aeng Tong-Tong village took the initiative by participating in events independently, namely participating in provincial and national Tourism Village competitions. Practical implications: However, there are several forms of government policies in supporting social policies such as participating in tourism village competitions, assistance with jamasan fees, and pelar agung. For now, the government's efforts in supporting the creation of environmental sustainability have not been felt by keris craftsmen. Because the focus of the local government for now only focuses on how to advance business development, namely by improving the economic performance of the kris craftsmen themselves. Originality/value: This research is considered very interesting to be carried out in Sumenep Regency considering the lack of research discussing Business Sustainability in the Sumenep area, as well as the number of MSMEs in Sumenep Regency will certainly feel the impact on the implementation of Business Sustainability.